The impact of coastal orography on profile wind - Moujane, Abderrahim; Bentamy, Abderrahim; Chagdali, Mohammed; Mordane, Soumia (International Journal of Advanced Geosciences, 2014)
The quality of the speed and direction of the surface wind issued from the regional model for weather forecasting "Aire Limitée Adaptation dynamique Développement International (ALADIN)", currently operational in the National Meteorological Direction (DMN), is studied in comparison with the 10 m observed speed and direction from meteorological stations and with new scatterometer wind products (QuikSCAT and Blended QuikSCAT). The series of average wind speed shows that ALADIN model could correctly reproduce the wind speed in the accented winds zones as well as in areas of reduced winds either on the coast or offshore (Moujane, et al, 2011). Some differences still existing between simulations and satellite measurements can be attributed to the nature of the QuikSCAT data used in this study. In fact, this data are daily, while the results of the ALADIN model are a grid values for each three hours reduced to a daily average. The simulated winds comply well reasonably with winds of QuikSCAT and QuikSCAT BLENDED throughout the study area, although significant differences are noted in the in situ and satellite observations. ALADIN model resolution is 0.17° whereas QUIKSCAT is only 0.5° and the spatial resolution of QUIKSCAT BLENDED is 0.25°, adding to these remarks the limitations of satellite measurement near the coast obtained with a precision of 2 ms-1. QuikSCAT face Aladin and QuikSCAT BLENDED confirm a high correlation reaching 0.9 throughout the area of study for the zonal and meridional wind component. Also, a high variability was observed with QuikSCAT compared to ALADIN and Blended during all seasons, it is of the order of 2 ms-1 to 2.5 ms-1 with a low difference of meridional wind which is about 0.5 ms-1 on the area of study found mainly near the coast in the north of the area. A marked relief effect was noticed in the figures of variability, which shows well the variability induced on the wind by the Caps, the bay and the islands. Keywords: Aladin, Blended, In-Situ, Orography, Quikscat, Wind.